Development of Sendang Gile Waterfall Tourism Object in Senaru Village, Bayan District, Lombok Utara Regency - Larastika Armili; Baiq Ismiwati; Lukman Hakim (Tinta Emas Publisher, 2024)
The Republic of Indonesia is a country that has the potential for abundant natural resources, biodiversity and historical/cultural heritage. This study aims to analyze the development of Sendang Gile Waterfall Tourism Object in Senaru Village, Bayan District, North Lombok Regency. This research uses a qualitative descriptive approach. Respondents were selected based on non-random sampling. Data analysis uses the Miles and Huberman model (Interactive Model) of the variables contained in the aspects of Attraction, Amenities, Access, and Anchilaris (4A Model) for the development of a tourist attraction. Data collection techniques used are observation, interview and documentation. Determination of informants in this study using snowball. The data validity method used is the triangulation method. The results of this study indicate that with the development of this waterfall tourist attraction, all existing obstacles can be resolved, which is indicated by the efforts that have been made by the managers starting from the rebuilding of tourist support facilities that were damaged by the earthquake. Then it can become a job opportunity for people who live in the waterfall tourism area.